Pemanfaatan Bahan Lokal Biji Pala (Myristica sp.) Sebagai Bahan Anestesi Pada Kegiatan Budidaya Ikan Hias Blue Devil (Chrysiptera cyanea) - Muhammad Aris; Fatma Muchdar (Fakultas Perikanan dan Ilmu Kelautan, Universitas Papua, 2021)
Blue Devil (Chrysiptera cyanea) is one of the very popular seawater ornamental fish commodities that is often sought after in international trade because of its attractive morphology. The trading ornamental fish commodities are very different from the consumption fish commodity because the trade is alive. Handling and transportation play a critical role in this system. However, the problem of delivering these goods is high mortality happened before the fish arrive at their destination. In this study, the delivery of ornamental fish using anesthetic ingredients. The anesthetic ingredients are MS-222, benzocaine, 2-phenoxyethanol, and quinaldine sulfate. The application of this material is not recommended because it will harm fish that can reduce fish immunity. The application of natural anesthetic ingredients can be used as an alternative environment. Nutmeg (Myristica sp.) is one of the local natural ingredients that have anesthetic potential. Nutmeg (Myristica sp.) contains essential oils that are useful as adaptive substances. This study aims to determine the potential of local Nutmeg (Myristica sp.) Seeds as an anesthetic material for Blue Devil (Chrysiptera cyanea) by lethal concentration / LC-50 testing. LC-50 testing in this study is an initial step to determine the appropriate anesthetic dose for Blue Devil (Chrysiptera cyanea). Making extracts from nutmeg seeds (Myristica sp.) Aims to obtain essential oils. The procedure for obtaining nutmeg (Myristica sp.) Essential oils are carried out by steam distillation. The results showed that the seeds of the Nutmeg plant (Myristica sp.) Were very influential for Blue Devil (Chrysiptera cyanea) with a very significant dose of 10ml, but not recommended for use. For development as an anesthetic material, then use a dose <2 ml.